2014
DOI: 10.1063/1.4875597
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive graphene Hall elements

Abstract: Hall elements were fabricated based on high quality chemical vapor deposition grown graphene, and their performance limit was explored. The as-fabricated graphene Hall element exhibits current-related sensitivity of up to 2093 V/AT under 200 μA, and magnetic resolution of around 1 mG/Hz0.5 at 3 kHz. This ultrahigh sensitivity and resolution stem from high carrier mobility, small Dirac point voltage of 3 V, and low carrier density of about 3 × 1011 cm−2 in graphene device. The current sensitivity is found to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 15 publications
5
65
0
1
Order By: Relevance
“…Therefore, the whole process of GHEs fabrications and modications is easy and compatible with silicon technology. 23 To investigate the surface topography of SMMs-modied graphene, we conducted an AFM test and the result is shown in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the whole process of GHEs fabrications and modications is easy and compatible with silicon technology. 23 To investigate the surface topography of SMMs-modied graphene, we conducted an AFM test and the result is shown in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
“…The Hall sensors with high sensitivity can detect magnetic eld with high signal-noise ratio and thus reduce the cost of amplications. 23,32 The absolute sensitivity (S A ) of GHEs is dened as the ratio of Hall voltage and external magnetic eld, 19,24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can then use (aa † + a † a)/2 = a † a + 1/2 = n + 1/2, which for the thermal state of the field at temperature T B has a value 1/2 (Muessel et al, 2014) BEC 2.5 × 10 −4 1.5 × 10 −6 1.5 × 10 −6 9.0 × 10 −17 · 1.9 × 10 −9 · 46 (Ahmadi et al, 2017) NVD 1.8 × 10 −5 1.8 × 10 −5 3.1 × 10 −3 3.5 × 10 −11 · 3.0 × 10 −9 · 47 (Kirtley, 2010) SQUID 6.5 × 10 −7 6.5 × 10 −7 · · 4.2 × 10 −13 · 1.8 × 10 −21 48 (Vasyukov et al, 2013) SQUID 1.6 × 10 −7 1.6 × 10 −7 · · 2.0 × 10 −14 · 1.0 × 10 −22 49 BEC 2.0 × 10 −6 2.0 × 10 −6 · · 4.0 × 10 −12 6.0 × 10 −9 · 50 (Wildermuth et al, 2004(Wildermuth et al, , 2005 BEC 3.0 × 10 −6 3.0 × 10 −6 3.0 × 10 −6 · · 2.2 × 10 −8 · 51 RFNVD 5.0 × 10 −7 5.0 × 10 −7 5.0 × 10 −7 · · 3.8 × 10 −8 · 52 (Vasyukov et al, 2013) SQUID 5.6 × 10 −8 5.6 × 10 −8 · · 2.5 × 10 −15 · 1.0 × 10 −22 53 RFNVD 4.0 × 10 −9 4.0 × 10 −9 · · 5.0 × 10 −17 · · 54 (Vasyukov et al, 2013) SQUID 4.6 × 10 −8 4.6 × 10 −8 · · 1.7 × 10 −15 · 1.0 × 10 −22 55 (Huang et al, 2014) GRA 1.6 × 10 −4 1.6 × 10 −4 · · · 1.0 × 10 −7 · 56 HALL 2.0 × 10 −7 2.0 × 10 −7 · · 4.0 × 10 −14 1.0 × 10 −7 · 57 RFNVD 3.0 × 10 −9 3.0 × 10 −9 · · 2.8 × 10 −17 · · 58 RFNVD 5.0 × 10 −9 5.0 × 10 −9 · · 7.9 × 10 −17 · · 59 (Forstner et al, 2014) WGM 4.0 × 10 −5 4.0 × 10 −5 4.0 × 10 −5 6.5 × 10 −14 · 1.4 × 10 −7 · 60 (Lima et al, 2014) MTJ 7.0 × 10 −6 7.0 × 10 −6 · · · 1.5 × 10 −7 · 61 RFNVD 5.0 × 10 −8 5.0 × 10 −8 5.0 × 10 −8 · · 2.9 × 10 −7 · 62 (Chenaud et al, 2016) HALL 1.0 × 10 −6 1.0 × 10 −6 · · · 3.0 × 10 −7 · 63 (Oral et al, 2002) HALL 1.5 × 10 −6 1.5 × 10 −6 · · · 6.0 × 10 −7 · 64 (Maletinsky et al, 2012) RFNVD 3.0 × 10 −9 3.0 × 10 −9 · · · 6.0 × 10 −6 · 65 (Kirtley, 2010) HALL 1.1 × 10 −7 1.1 × 10 −7 · · 1.2 × 10 −14 · 6.2 × 10 −18 66 (Kirtley, 2010) MFM 1.0 × 10 −8 1.0 × 10 −8 · · 1.0 × 10 −16 · 7.0 × 10 − 20 TABLE II Continuation of Table I.…”
Section: Appendix A: Thermal and Zero-point Magnetic Noiseunclassified
“…1 Recently, it has been shown that graphene can be an advantageous alternative to semiconductor materials for the development of high-sensitivity devices, due to its high room temperature carrier mobility, lowcost production and possibility of reducing the vertical distance between active layer and target. [2][3][4][5][6][7] Different device performances are expected, depending on the Hall bar geometrical properties and the graphene fabrication process, 2 e.g. chemical vapor deposition, molecular beam epitaxy on SiC and exfoliation.…”
Section: Introductionmentioning
confidence: 99%